2005
DOI: 10.1007/s10384-004-0213-5
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Nitric Oxide-Producing Cells in Normal and Diabetic Rat Retina

Abstract: NO might be produced in the GCL and amacrine cells, which show immunoreactivity to L-arginine, L-citrulline, and nNOS. In the early stage of diabetic retinopathy in STZ rat retinas, diabetes disturbed the function of the nNOS-positive amacrine cells and reduced NO production via nNOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…This parallels results in the retina during the early stages of STZ-induced diabetes 32 and underscores the contribution of nitric oxide to the pathogeneses of retinopathy in obese animals, as previously demonstrated in diabetic retinopathy in STZ rat retinas. 33 Notably, pericyte loss has also been described as an early pathological feature of diabetic retinopathy. 34 In close contact with retinal capillaries, these cells are important for the tightness of the inner blood-retina barrier 35 and for the integrity of the endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…This parallels results in the retina during the early stages of STZ-induced diabetes 32 and underscores the contribution of nitric oxide to the pathogeneses of retinopathy in obese animals, as previously demonstrated in diabetic retinopathy in STZ rat retinas. 33 Notably, pericyte loss has also been described as an early pathological feature of diabetic retinopathy. 34 In close contact with retinal capillaries, these cells are important for the tightness of the inner blood-retina barrier 35 and for the integrity of the endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…[202][203][204][205][206] As early as one to three weeks after STZ-induction, fewer eNOSand nNOS-positive cells were found in diabetic rat retina compared with control retina. 201,207 Abu El-Asrar et al 205 found elevated iNOS immunoreactivity in Müller cells in human diabetic retina. Müller cells span almost the entire width of the retina and are important for neuronal support.…”
Section: Nitric Oxidementioning
confidence: 99%
“…Hyperglycaemia increases iNOS activity, leading to excess nitric oxide, which is thought to contribute to diabetic retinopathy 202–206 . As early as one to three weeks after STZ‐induction, fewer eNOS‐ and nNOS‐positive cells were found in diabetic rat retina compared with control retina 201,207 . Abu El‐Asrar et al 205 found elevated iNOS immunoreactivity in Müller cells in human diabetic retina.…”
Section: Disease Mechanisms Common To Diabetes and Glaucomamentioning
confidence: 99%
“…NAC develop independent from retinal vascularization but their persistence in higher numbers than in the controls shows correlation to the reduced vascular stage of the retina. Retinae with increase of vascular supply like in diabetes show reduced numbers of NAC [11]. Since blood supply is correlated with the activity of the retina, light-dependent changes in NAC [12] might explain their modulating role for both, the neuronal aspects of the retina and the retinal vasculature.…”
Section: Brief Reportmentioning
confidence: 99%